2008
DOI: 10.1161/hypertensionaha.107.107821
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Dairy Products, Calcium, and Vitamin D and the Risk of Hypertension in Middle-Aged and Older Women

Abstract: Abstract-Prospective data on the associations between intake of dairy products and its nutrient components with risk of hypertension remain limited. We therefore investigated the associations of intake of dairy products, calcium, and vitamin D with the incidence of hypertension in a prospective cohort of 28 886 US women aged Ն45 years. Intake of dairy products, calcium, and vitamin D at baseline were assessed from semiquantitative food frequency questionnaires. Incident cases of hypertension (nϭ8710) were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
239
2
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(259 citation statements)
references
References 42 publications
11
239
2
7
Order By: Relevance
“…Findings of prospective cohort studies for the association of dairy intake with hypertension risk have been inconsistent (5)(6)(7)(8)(9)(10)(11). Some studies found an inverse association between higher dairy intake and hypertension risk (10,11), but others did not (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings of prospective cohort studies for the association of dairy intake with hypertension risk have been inconsistent (5)(6)(7)(8)(9)(10)(11). Some studies found an inverse association between higher dairy intake and hypertension risk (10,11), but others did not (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies found an inverse association between higher dairy intake and hypertension risk (10,11), but others did not (5)(6)(7)(8)(9). Higher low-fat milk intake was associated with lower increases in blood pressure in whites but not in African Americans, suggesting that ethnic differences may modify the association between dairy intake and blood pressure (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meat contains about 20 % protein and is rich in micronutrients such as zinc, iron, selenium, vitamins B 6 and vitamin B 12 , which make it as an important food item for human nutrition, especially in poor rural areas (3) . Nevertheless, excessive meat consumption leads to high intakes of saturated fat, dietary cholesterol and other substances associated with negative impacts on health (4) .…”
mentioning
confidence: 99%
“…Numerous epidemiological studies indicated that *Corresponding author: Y. Yang, email yxyang@263.net consumption of dairy products decreased levels of systolic blood pressure (12)(13)(14) , risk of type 2 diabetes and insulin resistance (15)(16)(17) , colorectal cancer (18) , as well as stroke and heart disease (16,17) .…”
mentioning
confidence: 99%